Thalassemia and the skeletal system: a clinical and radiological analysis - Adil, Raheela; Zulfiqar, Raja faisal; khoso, yousuf; korai, Shahid Maqbool; Kamran, Shahid; Baig, Imran Mehboob (International Journal of Pathology, 2025)
Background: Thalassemia can lead to various skeletal complications due to the effects of chronic anemia and iron overload. Common pathologies include bone deformities, osteoporosis, and fractures, particularly in the skull, long bones, and spine. Iron deposition in bones, coupled with abnormal bone marrow expansion, contributes to skeletal abnormalities. A comprehensive understanding of these skeletal manifestations is essential for improving management strategies and minimizing morbidity in thalassemia patients.Methods: It was an observational case control study and was hospital based, executed at department of Hematology mainly in collaboration with Medicine, Radiology and Pathology departments of (RYK Hospital, Rahim Yar Khan). Commencement of study took place on 12th of March 2022 and concluded on 11th of June 2023. Forty (40) patients and forty (40) controls participated in study. The data obtained was scrutinized by statistical package for social sciences software (SPSS) version 24. Dual-Energy X-ray Absorptiometry (DEXA) scans were generated for every case and control.Results: Our research found that people suffering from thalassemia have increased risk of weaker skeletal framework by -11.160 times at anatomical neck of femur and -6.670 times at vertebrae (lumbar) in comparison to controls. Cases versus control comparison of bone mineral density (BMD) also revealed a statistically highly significant difference also.   Conclusion: in light of our results, there is highly significant evidence that well above the half of the patients affected by thalassemia has weaker bones and should be evaluated and treated frequently for skeletal pathologies.